Defense Stability and Ecosystem Sustainability in the Strait of Malacca: Maritime Security Challenges from an International Relations Perspective - Awal Syahrul; Sumadinata R. Widya Setiabudi; Yani Yanyan Mochamad; Sudirman Arfin (E3S Web of Conferences)
This study examines the challenges of defense stability and ecosystem sustainability in the Strait of Malacca, one of the most strategic shipping lanes in the world. The strait plays a crucial role in global trade and geopolitics; however, the high volume of maritime traffic has led to issues such as maritime security threats, including piracy, smuggling, and geopolitical tensions, as well as environmental threats like marine pollution and ecosystem degradation. Cooperation between coastal countries such as Indonesia, Malaysia, and Singapore through the Cooperative Mechanism has successfully reduced security threats and environmental impacts, though significant challenges remain. The research employs a qualitative approach through literature reviews and document analysis. It focuses on the interaction between defense stability and ecosystem sustainability from an international relations perspective, including the role of security actors and environmental diplomacy. The findings reveal that defense stability in the Strait of Malacca is closely linked to regional cooperation and international power support. The use of advanced technologies such as satellite monitoring has enhanced maritime security, yet stronger environmental protection policies are still needed. In conclusion, the stability of the Strait of Malacca requires effective mitigation through cross-border cooperation, international policies, and enhanced monitoring technologies to safeguard this vital route for the global economy and the environment.